The social interaction between european community and communities in north borneo - Zainuddin, S.N.S.; Maureen De Silva (Quantum Academic, 2020)
This study focusing on the social interactions between the European community and the communities in North Borneo during the era of the British North Borneo Company from 1881 to 1941. This study identifies the interrelated factors between the European community and the communities in North Borneo. This study is specific to social interaction between European community with Chinese, Indians, Muruts, Dusun and Sulu’s people in North Borneo which began when these group was given the opportunity to hold positions in the British administration. Based on primary and secondary sources obtained from archives and libraries, the findings of the study found that the beginning of the relationship between the European community with the communities mentioned above is as soon as they work as subordinate workers. After that, the officials followed a lifestyle of the middle class in Europe as revealed by European administrative officials serving in North Borneo. They are not only exposed to the lifestyle of European officials’, but also the image and prestige. However, what limits the social interaction between the European community and the community in North Borneo is the cultural differences and social position in society. Therefore, this study would like to see the role of European community associations and clubs in North Borneo as it can improve the relationship between the European community and the community in North Borneo because, these associations and clubs not only accept non-European members, but also organize sports and leisure to all races, religions and genders. Therefore, this study would like to see the social interaction between the European community and the community in North Borneo which can be seen not only based on their relationship in clubs and associations as well as the relationship of European men and women in North Borneo.